Proceedings 2004 VLDB Conference 2004
DOI: 10.1016/b978-012088469-8/50084-x
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Framework for Grouping and Order Optimization

Abstract: Since the introduction of cost-based query optimization by Selinger et al. in their seminal paper, the performance-critical role of interesting orders has been recognized. Some algebraic operators change interesting orders (e.g. sort and select), while others exploit them (e.g. merge join). Likewise, Wang and Cherniack (VLDB 2003) showed that existing groupings should be exploited to avoid redundant grouping operations. Ideally, the reasoning about interesting orderings and groupings should be integrated into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…As such, some sort operations within the query execution plan become redundant and thus can be removed. Their work was followed and extended by [18,29,19], which are all independent and complementary to our work.…”
Section: Related Workmentioning
confidence: 96%
“…As such, some sort operations within the query execution plan become redundant and thus can be removed. Their work was followed and extended by [18,29,19], which are all independent and complementary to our work.…”
Section: Related Workmentioning
confidence: 96%
“…Earlier research has shown how to derive ordering and grouping properties for standard relational operators executed on non-partitioned inputs [15], [16], [17], [13], [12]. Ordering and grouping are local properties, that is, properties of each partition, so previous work still applies when the operators are running in partitioned mode.…”
Section: Deriving Structural Propertiesmentioning
confidence: 98%
“…Normalization and matching of local properties (sorting and grouping) have been studied extensively in [13], [12]. Matching of global properties (partitioning) is based on inference rules (2), (3), and (5) in section V. Recall that required properties are not always unique but may encode multiple alternatives, which results in additional matching opportunities.…”
Section: Property Matchingmentioning
confidence: 99%
See 2 more Smart Citations